Consumers' neutralization strategies to counter normative pressure: The case of illegal downloading. (March 2014) - Odou, Philippe; Bonnin, Gaël
The process of neutralization of normative pressure by consumers, which allows the performance of deviant practices while maintaining the attachment to the norm, has not been sufficiently studied. Our analysis, in the case of illegal downloading, shows that consumers produce an autonomous discursive set, articulated around three defensive strategies (disempowerment as neutralizing, pragmatic neutralization, ideological neutralization) and accept internal contradiction.